Improving Vocabulary Acquisition: Technology-Integrated, Gamified, and Contextualized Approaches in EFL Learning - Baiq Ika Aprianti, Baiq Ika Aprianti (Journal of Educational Studies, 2024)
The aim of this study is on contextualized, gamified, and technology-supported approaches to vocabulary learning in English as a Foreign Language (EFL) situation. Contextualized learning greatly improves understanding and retention by placing terminology in relevant contexts. Quizlet and other gamified tools increase vocabulary acquisition and student motivation, while multimedia resources like movies with subtitles enhance receptive vocabulary and cultural knowledge. According to quantitative pre- and post-test results and qualitative data from interviews conducted using a mixed-methods approach, cooperative and culturally sensitive approaches promote participation and useful language usage. Blended approaches that combined conventional and digital methods proven to be quite successful in spite of obstacles including disparities in digital literacy and unequal access to technology. These results demonstrate how flexible instructional approaches are necessary to meet the demands of a wide range of students. The study results to the conclusion that EFL vocabulary training may be revolutionized by integrating contextualized, interactive, and technology-enhanced approaches. To guarantee inclusive education for all students, recommendations include removing obstacles to technology access and conducting further research on scalable approaches.